Life beyond the care center: the lived experience of care leavers in Vietnam - Gilligan, Robert (My University, 2025)
There is strong evidence across many countries that young people transitioning out of alternative care at the relevant local legal care leaving age face considerable challenges as they adapt to life beyond their previous care settings. While there is a growing body of work examining their experiences in countries in the Global North, there are fewer studies reporting on care leaver experiences in the Global South. This study is based on semi-structured qualitative interviews with 25 care leavers in Vietnam. It explores their experience of adapting to life beyond their care center. While many of the participants report varying degrees of positive progress, the study also reveals the considerable challenges they may encounter in relation to accommodation, work and education. There was also evidence of the emotional pressures of negotiating these issues, the concerns that might arise in relation to their social and family relations, and the stigma felt to be associated with their ex-care status. While some proved adept at finding their way and identifying sources of support (sometimes linked to connections though the care centre), for others the precarity of their daily circumstances was an ongoing pressure. Analysis revealed how agentic the young people were, but also how important support was to sustain such agency. Access to work was an especially critical issue.
PUBLISHED
Keywords: Care leavers; Vietnam; Lived experiences; Agency; Support; Precarity